HUBUNGAN PENGETAHUAN SUAMI DAN BUDAYA DENGAN KEJADIAN UNMED NEED KELUARGA BERENCANA - Noflidaputri, Resty (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Bukittinggi is the highest unmet need especially in Mandiangin Koto Selayan. It was about S36.98%. There are many factors related to unmet need such as lack of knowledge about family planning and cultural factors by couples of childbearing age (EFA). This research aimed to determine The Correlation between Husband’s Knowledge and Culture toward Unmet Need for Family Planning in Manggis Ganting, Mandiangin Koto Selayan, Bukittinggi 2019.The design of this research was descriptive analytical to Male PUS. It was conducted on January 10 to January 23 2019 in Manggis Ganting, Mandiangin Koto Selayan Sub-district. They were 70 people there. Then, systematic random sampling technique had been used to take the samples. The data were collected trough questionnaires and it was with analyzed by computerized with univariate and bivariate analysis (chi-square test).The results of univariate analysis obtained that 72.9% of them had good knowledge. Then, 68.8% of the respondents stated that they did not supported by the cultures. After that, 67.1% of them had unmet need for family planning. Moreover, there was no relationship of knowledge (p value = 0.833) with the incidence of unmet need for family planning but there was a significant relationship between cultures (p value = 0.004 and OR 0.182) with the incidence of unmet need for family planning.In short, it can be concluded that culture had an influence on the use of contraception, because there was a culture that does not support family planning so there is an incident of unmet need for family planning. Then, it is expected to health workers to improve health services especially those related to contraception through referral and socialization through the leaders of community and religious. Keywords : Culture, Contraception, Knowledge, Male PUS, Unmet Need